2005
DOI: 10.1038/sj.leu.2404050
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of combination transcriptional modulation therapy with sodium phenylbutyrate and 5-azacytidine in patients with acute myeloid leukemia or myelodysplastic syndrome

Abstract: Epigenetic mechanisms underlying tumorigenesis have recently received much attention as potential therapeutic targets of human cancer. We designed a pilot study to target DNA methylation and histone deacetylation through the sequential administration of 5-azacytidine followed by sodium phenylbutyrate (PB) in patients with acute myeloid leukemia (AML) or myelodysplastic syndrome (MDS). Ten evaluable patients (eight AML, two MDS) were treated with seven consecutive daily subcutaneous injections of 5-azacytidine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(61 citation statements)
references
References 27 publications
2
58
0
1
Order By: Relevance
“…A pilot study combining phenylbutyrate (HDI) with 5-azacitidine showed that both complete and partial remissions could be achieved in nearly half of the MDS and AML patients and showed a strong association between the clinical responses and changes in hypermethylation and expression of p15 [200]. The clinical responses were supported with findings from a second pilot study of the same combination [201]. Gore et al combined MS-275 (HDI) with 5-azacitidine (DMTI) in a follow-up pilot study recently presented in abstract form at ASH 2006 2 .…”
Section: Epigenetic Treatments -Expanding Targetssupporting
confidence: 71%
“…A pilot study combining phenylbutyrate (HDI) with 5-azacitidine showed that both complete and partial remissions could be achieved in nearly half of the MDS and AML patients and showed a strong association between the clinical responses and changes in hypermethylation and expression of p15 [200]. The clinical responses were supported with findings from a second pilot study of the same combination [201]. Gore et al combined MS-275 (HDI) with 5-azacitidine (DMTI) in a follow-up pilot study recently presented in abstract form at ASH 2006 2 .…”
Section: Epigenetic Treatments -Expanding Targetssupporting
confidence: 71%
“…Cameron et al (1999) first reported the synergistic effect of DNMT inhibitors with HDAC inhibitors on global acetylation of histones H3 and H4. This was also detected in vivo in peripheral blood leukocytes from AML/MDS patients undergoing treatment with the DNMT inhibitor 5-azacytidine and the HDAC inhibitor sodium PB (Gore et al, 2006;Maslak et al, 2006), and with decitabine and VPA (Garcia-Manero et al, 2006;Blum et al, 2007).…”
Section: Discussionmentioning
confidence: 80%
“…This approach, however, is not effective on ATRA-resistant APL forms and other AML (non-APL) subtypes [3], which are refractory to ATRA-induced differentiation [4]. Therefore, the current treatment for the bulk of the other AML subtypes still consists of high-dose chemotherapy with potential lifethreatening toxicity and acquired drug resistance [5].Inhibitors of histone deacetylases [6] and DNA demethylating agents [7,8] 2009;37:1176-1185 [9], thus providing additional tools for cancer therapy [10]. Indeed, epigenetic modulators are functional to set up an environment permissive for cell differentiation and/or apoptosis, but may not always be sufficient themselves to trigger these processes without the cooperation of other proactive signals.…”
mentioning
confidence: 99%